Integrated fault diagnosis and control design of linear complex systems - Davoodi, Mohammad Reza; Meskin, Nader; Khorasani, K. 1960- (IET control, robotics and sensors series ;, 2018)
This book addresses the design challenges of developing and implementing novel integrated fault diagnosis and control technologies for complex linear systems.